Exploring First-Time Voters' Perceptions of Multiculturalism and Identity Politics in Indonesia’s 2024 General Election - Gaspersz, Steve Gerardo Christoffel; Basuki, Eko; Maspaitella, Marthin Jonas (Jurnal Pendidikan Multikultural Indonesia, 2024)
This article is based on research aimed at understanding the perceptions of the millennial generation as first-time voters in the 2024 Indonesian General Election, while also exploring their concerns regarding participation in this democratic event. The study seeks to analyze high school students' perceptions of multiculturalism and identity politics through their roles as novice voters in the 2024 election. Employing a mixed-methods approach, data were collected from 100 high school students through surveys (questionnaires) and interviews, then classified and interpreted to gain insights into their perceptions of the role of first-time voters in the electoral process. The study reveals three key findings: perceptions of multiculturalism, perceptions of identity politics, and perceptions of agency-structure roles. The article concludes that first-time voters from the high school student demographic view youth political participation in Indonesia as a critical issue that warrants significant attention from the government. Strengthening their capacity as first-time voters ahead of the 2024 election is essential, particularly through enhancing their knowledge of democratic rights as citizens and introducing them to prospective leaders at both executive and legislative levels. This capacity-building effort is expected to foster a healthy political education environment that supports the sustainability of democracy and tolerance in Indonesia. Moreover, the study highlights the need to address the intensity and infiltration of identity politics narratives through social media, which have the potential to create social polarization, especially among Indonesia's younger generation.